Study of long-range dispersion for Cesium-137 in Southeast Asia - Soh, Rachel Li Yi (Nanyang Technological University, 2022)
The nuclear crisis in 2011 at Fukushima Daiichi Nuclear Power Plant (NPP) has brought greater awareness to safety issues of NPP. Long half-life radionuclides can be transported in the atmosphere and across oceans for long distances, which can exceed thousands of kilometers and allow effects of radioactive fallout to be more widespread. Recently, an increasing number of countries in Asia have been actively exploring the adoption of nuclear energy due to increasing energy demands and the drive to reduce greenhouse gas emissions. In this project, we study the long-distance atmospheric dispersion behaviour of Cesium-137 in Southeast Asia, where Cesium-137 is a common radionuclide released during NPP accidents and has a relatively long half-life of 30 years. The HYSPLIT, a Lagrangian atmospheric dispersion model developed by NOAA Air Resources Laboratory, will be used to simulate the long-range dispersion processes in the Southeast Asia region. Numerical experiments will be conducted to study the concentration-distance relationship and the sensitivity of using different release scenarios or model parameters.